Association between mossy fiber sprouting and expression of semaphorin-3f protein in dentate gyrus of hippocampus in lithium-pilocarpine-induced status epilepticus mouse model. (1st November 2016) - Cai, Xiaodong; Long, Ling; Yang, Libai; Chen, Ziyi; Ni, Guanzhong; Qin, Jiaming; Zhou, Jueqian; Zhou, Liemin
Abstract : Objectives: Mossy fiber sprouting is involved in the pathogenesis of mesial temporal lobe epilepsy. But the exact mechanism of formation of mossy fiber sprouting is still unclear. Semaphorin-3f protein could inhibit the growth of neuron axons. The aim of this research is to evaluate the association between semaphorin-3f expression and mossy fiber sprouting. Methods: We established pilocarpine-induced status epilepticus (PISE) models firstly. Then, mossy fiber sprouting in the hippocampus of PISE models was examined by Timm staining. Expression of semaphorin-3f was evaluated by western blot analysis and immunohistochemical examination. Expression of semaphorin-3f protein in different subregions of hippocampus and its relationship with mossy fiber sprouting were studied. Results: We found that in PISE group, mossy fiber sprouting appeared in dentate gyrus (DG) region. It started to develop in the latent phase of PISE group and increased significantly in the chronic phase. Expression of semaphorin-3f protein in DG region started to decrease in the latent phase, and stayed at low level in the chronic phase. No such change was found in the other groups. Conclusions: These results indicate that the decrease in semaphorin-3f expression in DG region was in parallel to the change of mossy fiber sprouting in PISE models, suggesting that mossy fiber sprouting is closely associated with reduced expression of semaphorin-3f in this model.